Footwall Geology and Deformation at Flip‐Flop Mid‐Ocean Ridge Detachment Faults: 64°35′E Southwest Indian Ridge (SWIR) - S. Mahato; M. Cannat (Geochemistry, Geophysics, Geosystems)
Abstract Using bathymetry and ROV dives, we investigate two successive flip‐flop detachment faults (D1 active, D2 older) in the near‐amagmatic 64°35′E region of the SWIR. Kilometer‐sized benches on the upper slopes of D1 footwall form the D1 degraded breakaway. Scarps at the top expose the D2 fault zone with deformed serpentinized peridotite, sigmoidal phacoids, planar fractures, and serpentinite microbreccia/gouge horizons. Two ROV sections of the D1 footwall show contrasting deformation styles, corresponding to distinct morphological domains, which relate to contrasting fault and footwall strength. One section documents corrugations, outcrops dominated by sigmoidal phacoids, and planar fractures with thin, discontinuous serpentinite microbreccia/gouge horizons. ROV dives in this corrugated domain show that NNE‐trending km‐spaced ridges and WNW‐trending narrow benches in the shipboard bathymetry correspond, respectively, to broad undulations (mega‐corrugations) of the D1 fault and to several antithetic minor normal faults (cumulated horizontal offset of ∼285 m). The other section, lacking corrugations, broad ridges, and antithetic fault, has thicker and more continuous serpentinite microbreccia/gouge horizons, indicating a weaker fault. The abundance of such weak gouges probably reflects hydrous fluid availability during deformation. We link mega‐corrugations in the western domain and km‐scale lobes of D1 emergence to a broad detachment damage zone with up to ∼600 m‐thick mega‐phacoids of less deformed serpentinized peridotite. Small antithetic normal faults in the corrugated domain are interpreted as due to bending forces in the D1 footwall. Our findings highlight the three‐dimensional, non‐planar structural and morphological variability of the exhumed D1 detachment fault zone along the ridge‐axis.